PENGARUH BIAYA DISTRIBUSI DAN BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. KIMIA FARMA INDONESIA (PERSERO) TBK. PERIODE 2009-2016 - Nasser Hasibuan, Abdul (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
PT. Kimia Farma is the first pharmaceutical industry company in Indonesia which was established by the Dutch East Indies Government in 1817. Where the purpose of this company is to generate profit for survival and collect enough funds for implementing business activities. To achieve this profit, of course, it must improve product quality and increase sales volume. Sales volume of PT. Kimia Farma Indonesia experienced fluctuations in 2009-2016. The formulation of the problem from this study is whether there is an influence of distribution costs and promotion costs on sales volume at PT. Kimia Farma Indonesia Tbk in 2009-2016. Then the goal is to find out the effect of distribution costs and promotion costs on sales volume at PT. Kimia Farma Indonesia Tbk in 2009-2016.The discussion in this study relates to financial accounting especially in the focus of cost accounting and financial management. Where will be discussed about distribution costs and promotion costs and their effects on sales volume. This research is quantitative with a type of comparative causal research. The research sample is population research, sampling techniques with purposive sampling method. Source of data from the financial statements of PT. Kimia Farma Indonesia Tbk which is published on the Indonesia Stock Exchange with the website www.idx.com. Data is processed using the SPSS Version 22 program by carrying out descriptive statistical tests, normality tests, multicollinearity tests, autocorrelation tests, heterocedasticity tests, multiple regression analysis, t test, F test, and determinant coefficient test. Based on the results of the study, it can be concluded that the results of the study are partial (T test) stating that the tcount t table (2.788 2.045) and significance 0.05 (0.04 0.05), the distribution cost variable affects the sales volume in 2009-2016. While the variable cost of promotion is very influential on sales volume with a tcount ttable (18,540 2,045) with a significance of 0.05 (0,000 0,05). Simultaneously (F test) states that distribution costs and promotion costs together (simultaneous) affect the sales volume with a value of F_count F table (196.662 3.328) with a significance of 0,000 with a significance level of 5%.